The Function of The Kinship Legal System and Legal Certainty of Land Rights of Papuan Customary Communities in Jayapura City (From a Philosophical, Sociological, and Legal Perspective) - Frans Reumi; Farida Kaplele; Tom Alfa Samuel Reumi (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This study aims to analyze the function of the kinship legal system in regulating land rights for Papuan customary communities in Jayapura City, identify factors causing legal uncertainty, and formulate a policy model that can guarantee legal certainty of these land rights. This study uses philosophical, sociological, and juridical approaches to understand the role of values, social structures, and formal legal norms in the dynamics of customary land ownership. The findings indicate that the kinship legal system, particularly those based on patrilineal and matrilineal descent, remains the primary basis for recognizing land rights at the community level. However, the weak formal state recognition of this system, overlapping sectoral regulations, the absence of customary territory mapping, and limited community access to legal justice are the main causes of legal uncertainty. To address these issues, this study proposes a hybrid policy model that integrates formal legal recognition of customary rights, participatory mapping, strengthening customary institutions, and the implementation of the principle of Free, Prior, and Informed Consent (FPIC) throughout the licensing and development process. The results of this study emphasize the importance of synchronizing state law and customary law within the framework of Papua's Special Autonomy in order to create legal certainty that is just and contextual.